Relationship between ALDH2 genotype and in-stent restenosis in Chinese Han patients after percutaneous coronary intervention - Lizhi Lv; Weijie Ye; Peiyuan Song; Yubin Chen; Jing Yang; Congmin Zhang; Xiaoping Chen; Fanyan Luo (BMC Cardiovascular Disorders, 2019)
Abstract Background It is well known that the genotype of ALDH2 is associated with coronary artery disease (CAD), and in-stent restenosis (ISR) is a primary complication of percutaneous coronary intervention (PCI), a primary recommended treatment for CAD. The aim of this study was to identify the relationship between aldehyde dehydrogenase 2 (ALDH2) genotype and in-stent restenosis (ISR). Methods This study recruited 531 patients who were undergoing PCI at two Chinese hospitals from 2015 to 2017 and 183 were diagnosed with ISR after PCI during the one-year follow-up period. We used polymerase chain restriction fragment length polymorphism (PCR-RFLP) and sequencing to determine ALDH2 polymorphisms. Results Among all 531 patients (mean age = 59.4 ± 9.8; 65.9% male), 68.7% carried the wild-type genotype, 28.4% were heterozygous for the mutation, and 2.8% were homozygous for the mutation. Multiple logistical regression analyses indicated no correlation between ALDH2 genotype and the occurrence of restenosis after PCI (OR = 1.448, 95% CI: 0.965–2.168, p = 0.073), though a significant association was observed for patients with diabetes (OR = 4.053, 95% CI: 1.668–10.449, p = 0.003). Conclusion In this study, we found that carrying an ALDH2*2 allele had no notable relationship with ISR one year after PCI but that it did have a significant association with complications in diabetic patients. Further studies with larger sample sizes will be necessary to reveal a consensus.